How drawing practice enhances distress tolerance in university students: the mediating roles of psychological resilience and self-disclosure - Ziwei Lyu; Shuangping Ouyang; Shuxin Zhang (Frontiers in Psychology, 2025)
IntroductionUniversity students often face significant academic and emotional pressures, making distress tolerance a vital skill for maintaining mental wellbeing. Drawing practice, as a creative outlet, has been shown to promote emotional regulation and psychological health. This study examines how drawing practice influences distress tolerance, focusing on the mediating roles of psychological resilience and self-disclosure.MethodsThis study recruited 354 university students from Hunan Province, China, using a combination of convenience sampling and snowball sampling methods to ensure a diverse and representative participant pool. These approaches facilitated efficient data collection while capturing varied student experiences. To test the proposed hypotheses, a structural equation model (SEM) was developed and analyzed using AMOS, allowing for a robust evaluation of the relationships among the variables.ResultsThis study examined the relationship between drawing practice and distress tolerance, focusing on the mediating roles of psychological resilience and self-disclosure. The results indicated that drawing practice is associated with higher psychological resilience and greater self-disclosure, both of which are linked to improved distress tolerance. These findings underscore the indirect pathways connecting drawing practice to distress tolerance.DiscussionThis study highlights how drawing practice contributes to university students' ability to manage academic and emotional pressures by fostering psychological resilience and encouraging self-disclosure, both of which are linked to better distress tolerance. These findings demonstrate the potential of creative activities like drawing to support university students' mental wellbeing, providing valuable insights for promoting emotional health in high-stress academic environments.